Gedachtes wohnen: Heidegger and cultural geography - Paddock, Troy (Philosophy & Geography, 2004)
Keywords: cultural geography; dept.his

Still stuck at sevastopol: the depiction of russia during the russo-japanese war and the beginning of the first world war in the german press - Paddock, Troy (German History, 1998)
Keywords: dept.his

Spatial relations and the struggle for space: Friedrich Ratzel’s impact on German education from the Wilhelmine Empire to the Third Reich - Paddock, Troy (Journal of Educational Media, Memory, and Society, 2016)
This article examines the influence of Friedrich Ratzel’s idea of the struggle for space and its impact on cultural and national development depicted in German geography and history textbooks from the Wilhelmine era to the Third Reich. Ratzel’s concept of bio-geography conceived the state as a living organism that is the product of humanity’s interaction with the land and also facilitates humanity’s spread across the earth. German textbooks promoted a similar concept of the state in their portrayal of geography and history, the implications of which were appropriated by the National Socialists to support their geopolitical goals.
Keywords: Education; Friedrich ratzel; Geography instruction; History instruction; National identity; State; Textbooks; dept.his

Russia in the German global imaginary: imperial visions and utopian desires, 1905-1941 - Paddock, Troy (First World War Studies, 2023)
Keywords: book.review; dept.his

British first world war propaganda: from A to Z - Paddock, Troy (First World War Studies, 2026)
Keywords: dept.his

Rolf Brandt and a conservative literary journalism - Paddock, Troy RE (Literary Journalism Studies, 2019)
Rolf Brandt (1886-1953) was a German journalist, author, and political commentator. His first work was as a war reporter on the Eastern Front during the opening months of the Great War (World War I). His reports appeared in several important German newspapers (Norddeutsche Allgemeine Zeitung and Frankfurter Zeitung) and were compiled and published in 1915 as Fünf Monate an der Ostfront: Kriegsberichte (Five months on the Eastern Front: War reports). Brandt's reports were more than just army-approved press releases. He wrote in a way that constructed a bridge between the home front and the front lines. In the process he employed techniques now associated with literary journalism. With a clear point of view, he told his story through a sequence of scenes, instead of a simple historical narrative, and included genuine dialogue and status details. While scholars of German literary journalism point to Egon Erwin Kisch as the originator of German literary journalism, this study suggests Brandt should be considered an early practitioner of literary journalism in the German language. More interestingly, Brandt's particular brand of literary journalism had an unmistakably conservative nationalist perspective, thus suggesting that it is possible to have a conservative form of literary journalism. © 2019 Literary Journalism Studies. All Rights Reserved.
Keywords: Conservative literary journalism; Germany; Propaganda; Rolf Brandt; Russia; World War I; dept.his; peer-reviewed; ⛔ No DOI found

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge, 2019)
Contesting the Origins of the First World War challenges the Anglophone emphasis on Germany as bearing the primary responsibility in causing the conflict and instead builds upon new perspectives to reconsider the roles of the other Great Powers. Using the work of Terrance Zuber, Sean McMeekin, and Stefan Schmidt as building blocks, this book reassesses the origins of the First World War and offers an explanation as to why this reassessment did not come about earlier. Troy R.E. Paddock argues that historians need to redraw the historiographical map that has charted the origins of the war. His analysis creates a more balanced view of German actions by also noting the actions and inaction of other nations. Recent works about the roles of the five Great Powers involved in the events leading up to the war are considered, and Paddock concludes that Germany does not bear the primary responsibility. This book provides a unique historiographical analysis of key texts published on the origins of the First World War, and its narrative encourages students to engage with and challenge historical perspectives.
Keywords: dept.his

World War I and Propaganda - Paddock, Troy R. E. (History of warfare, 2014)
World War I and Propaganda offers a new look at a familiar subject. The contributions to this volume demonstrate that the traditional view of propaganda as top-down manipulation is no longer plausible. Drawing from a variety of sources, scholars examine the complex negotiations involved in propaganda within the British Empire, in occupied territories, in neutral nations, and how war should be conducted. Propaganda was tailored to meet local circumstances and integrated into a larger narrative in which the war was not always the most important issue. Issues centering on local politics, national identity, preservation of tradition, or hopes of a brighter future all played a role in different forms of propaganda. Contributors are Christopher Barthel, Donata Blobaum, Robert Blobaum, Mourad Djebabla, Christopher Fischer, Andrew T. Jarboe, Elli Lemonidou, David Monger, Javier Pounce,Catriona Pennell, Anne Samson, Richard Smith, Kenneth Andrew Steuer, María Inés Tato, and Lisa Todd.
Keywords: dept.his

Creating the Russian Peril: Education, the Public Sphere, and National Identity in Imperial Germany, 1890-1914 - Paddock, Troy R. E. (Camden House, 2010)
German attitudes toward and stereotypes of Russia before the First World War and how they were inculcated in the public.
Keywords: 1871-1918; 19th century; Education; 19th century; Nationalism; 20th century; Germany; 20th century; Nationalism; Foreign public opinion, German; Russia; Germany; Germany; Germany; Germany; Russia; History; History; Education; Political aspects; Press coverage; Public opinion; Relations; Russia; Russia; SCSU Faculty Scholar Award; award_winner; dept.his; faculty_collection

A Call to Arms: Propaganda, Public Opinion, and Newspapers in the Great War - Paddock, Troy R. E. (Perspectives on the twentieth century, 2004)
World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t., World War I highlighted the influence of newspapers in rousing and maintaining public support for the war effort. Discussions of the role of the press in the Great War have, to date, largely focused on atrocity stories. This book offers the first comparative analysis of how newspapers in Great Britain, France, Russia, Germany, and Austria-Hungary attempted to define war, its objectives, and the enemy. Presented country-by-country, expert essays examine, through use of translated articles from the contemporary press, how newspapers of different nations defined the war for their readership and t
Keywords: Press coverage; Propaganda; World War, 1914-1918; Public opinion; Press and propaganda; War; World War, 1914-1918; dept.his; faculty_collection

“No Man’s Land”: Forbidden and Subversive Space in War - Paddock, Troy R. E. (Environment, Space, Place, 2013)
Keywords: dept.his

Bridges: Technology and the Social - Paddock, Troy R. E. (Environment, Space, Place, 2010)
Keywords: dept.his

Sabbatical report on Contesting the Origins of the First World War - Paddock, Troy R. E. (2019)
Dr. Paddock spent the year completing a book and revising an article.
Keywords: dept.his; faculty_collection; sabbatical_report

World War I and Propaganda - Paddock, Troy R. E. (History of warfare ; v. 94, 2014)
Keywords: Propaganda; World War, 1914-1918; dept.his; faculty_collection

Contesting the Origins of the First World War: An Historiographical Argument - Paddock, Troy R. E. (Routledge studies in modern history, 2020)
Keywords: Causes; Historiography; Historiography; World War, 1914-1918; World War, 1914-1918; dept.his; faculty_collection

Is one world enough for all of us?: Thoughts on globalization - Paddock, Troy R. E. (Dangers in the incommensurability of globalization: socio-political volatilities, 2008)
Keywords: dept.his

Chronoscapes/chronos escapes: a meditation on historical time - Paddock, Troy R. E. (Ecoscapes: geographical patternings of relations, 2006)
Keywords: dept.his

Land makes the man: topography and national character in german school books - Paddock, Troy R. E. (Lived topographies and their mediational forces, 2005)
"This collection explores the various forms of narrative, semiotic, and technological mediation that shape the experience of place. From the East End of London to Navajo lands to Ground Zero, Lived Topographies examines the great effect of language, mass media, surveillance, and other incursions of the contemporary world on topographical experience and description. Gary Backhaus and John Murungi have assembled a wide array of scholars to provide an interdisciplinary approach to this subject, giving this collection a unique perspective on the phenomenology of place."--Jacket.
Keywords: dept.his